The impact of structured clinical supervision on nurses’ adherence to nutritional education protocols for cardiac inpatients: A quasi-experimental study - Wiwiek Delvira; Sri Puguh Kristiyawati; Zaenal Muttaqin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Nutritional education is crucial for managing cardiovascular diseases; however, nurses’ adherence to established protocols remains suboptimal. This study aimed to evaluate the effectiveness of clinical supervision in improving nurses’ compliance with providing nutritional education to hospitalized cardiac patients. A quasi-experimental pre–post design was applied, involving 38 nurses working in the cardiac ward of a Type B General Hospital in Riau Province, from March to May 2024. The intervention group received structured clinical supervision for four weeks, while the control group continued with the standard procedures. Compliance was measured using validated observation and self-report instruments. Data were analyzed using paired t-tests and ANCOVA. Results showed that. The mean compliance score in the intervention group increased from 68,4 (SD = 8,7) to 88,2 (SD = 6,3) (p < 0,001), whereas no significant change was observed in the control group. ANCOVA confirmed that clinical supervision had a significant effect on compliance (F = 11,23, p = 0,002), with a large effect size (η² = 0,24). In conclusion, clinical supervision effectively improved nurses’ compliance in providing nutritional education. Integrating structured supervision into nursing management may enhance the quality of patient education and support better clinical outcomes in the future.